KEEFEKTIFAN PENGGUNAAN TEKNIK DERET KATA DALAM PEMBELAJARAN MENULIS KREATIF PUISI - Anggraini, Tri Riya (Lentera: Jurnal Ilmiah Kependidikan, 2019)
The attitude of students' disinterest and the inaccuracy of the teacher in choosing techniques or learning methods for learning to write poetry, it is necessary to research effective learning techniques for learning to write poetry. This study also aims to determine the effectiveness of the use of word series techniques in improving the ability to write creative poetry. The results showed a significant difference in the posttest scores of creative writing poetry of the control group and experimental group students. In the control group there were 6 students who got low scores, 29 students got medium scores, and 2 students got high scores. In the experimental group there were 2 students who got low scores, 18 students got medium scores, and 15 students got high scores. This shows that there are significant differences in the ability to write creative poetry between the control group and the experimental group. The t-test results of the pretest and posttest scores of the experimental group produced a tcount of 2007 with a df of 35 and a table of 0.13 at a significance level of 5%. This shows that the effective word series technique is used in learning to write poetry because the value of t-count <-table (-2.007 <- 0.13).